The effect of income-based policies on mortality inequalities in Scotland: A modelling study - Elizabeth Richardson; Lynda Fenton; Jane Parkinson; Andrew Pulford; Martin Taulbut; Gerry McCartney; Mark Robinson (University of Essex, Institute for Social and Economic Research (ISER), 2020)
The unequal distribution of income is a fundamental determinant of health inequalities. Decision making around economic policies could be enhanced by showing their potential health effects. We used scenario modelling to assess the effects of 12 income-based policies on Years of Life Lost (YLL) and inequalities in YLL in Scotland. EUROMOD, a tax-benefit microsimulation model, was used to estimate the effects of hypothetical fiscal policies on income for Scottish households (n=2871; 2014/15 Family Resources Survey). Income change was estimated for each quintile of the 2016 Scottish Index of Multiple Deprivation. 'Triple I', a health inequalities scenario modelling tool, was used to estimate policy effects on YLL and government spending after 5 years. The best policy for improving health and narrowing health inequalities was a 50% increase to means-tested benefits rates (approximately 105,177 or 4·7% YLL fewer than the baseline scenario, and a 7·9% reduction in relative index of inequality (RII)). Citizen's Basic Income (CBI) schemes also substantially narrowed inequalities (3·7% RII for basic scheme, 5·9% for CBI with additional payments for disabled individuals), and modestly reduced YLL (0·7% and 1·4%, respectively). The most effective policies for reducing health inequalities appeared to be those that disproportionately increased incomes in the most deprived areas.
Keywords: D31; I14; I38; 330; income distribution; health inequalities; multiple deprivation; Scotland